2020
DOI: 10.1136/bmjinnov-2019-000370
|View full text |Cite
|
Sign up to set email alerts
|

Switching among branded and generic medication products during ongoing treatment of psychiatric illness

Abstract: Switches between branded (reference) medications and the corresponding generic medications or between two different corresponding generic medications occur commonly during the treatment of central nervous system disorders. Prescribing a generic product in place of a reference product can reduce patient and pharmacy costs. But there can be implications. Planned or unplanned switches from one product to another during ongoing treatment may introduce variability in drug exposure which could in turn compromise eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Instead most BE studies are performed on a small number (12–36) of young, healthy volunteers who are predominantly male and White. These research participants are not representative of the patients who will eventually take the medication 14 . Moreover, current regulations do not require BE studies comparing different generic versions, so variability in the dose of the active pharmaceutical ingredient (API) can be greater between these formulations than between each generic and the brand-name drug 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead most BE studies are performed on a small number (12–36) of young, healthy volunteers who are predominantly male and White. These research participants are not representative of the patients who will eventually take the medication 14 . Moreover, current regulations do not require BE studies comparing different generic versions, so variability in the dose of the active pharmaceutical ingredient (API) can be greater between these formulations than between each generic and the brand-name drug 11 …”
Section: Discussionmentioning
confidence: 99%
“…These research participants are not representative of the patients who will eventually take the medication. 14 Moreover, current regulations do not require BE studies comparing different generic versions, so variability in the dose of the active pharmaceutical ingredient (API) can be greater between these formulations than between each generic and the brand-name drug. 11 In addition, active ingredients make up a very small proportion of what is contained in most medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PK for these 2 hypothetical generics would result in very different drug exposures. 16 Results from one review that included antiepileptics, antipsychotics, antidepressants, benzodiazepines and psychostimulants concluded that changes in PK resulting from a switch from a branded to a generic psychotropic medication are generally unlikely, but possible in some patients. It was also noted that switches among generics may result in PK changes exceeding ±20 % in instances where each generic differs from the reference drug in opposing directions.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%